Relatório de Estágio Profissional - Uma Longa Caminhada - Do Sonho de Criança à Realidade de Adulto" - Jorge Leandro Carneiro da Silva (2019)
The Professional Internship is the last step that the student has to fulfill to finish his initial formation and become a teacher. This period of time is fundamental for the professional growth of the student, because during it he will be able to know the real world of teaching, and will be able to put into practice everything he has retained in theory. This document is where all the experiences, errors and reflections related to this long journey will be presented. To be easier to understand, I will describe the organization of this document. It is divided into 6 chapters: the first is the Introduction, a space in which the Stage is performed and contextualized; The second is the Personal Framework, where the objective was to describe the course, personal and academic, and to identify the expectations regarding the Internship; The third chapter, the Practice Framework, will be the contextualization of the place where the Internship took place, focusing on various aspects, such as the school, the internship nucleus, and the Cooperating Teacher and the Guiding Teacher; then chapter four, Realization of Professional Practice, which reports all lived experiences, problems encountered and how to overcome them; The fifth chapter presents the action research study, which aims to verify whether there is a relationship between physical activity outside the school context and student achievement; Finally, the last chapter will focus on the conclusions of this document and future perspectives.